An integrated system for ammonia production from renewable hydrogen: A case study - Ozturk, Merve; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study presents an analysis and assessment study of an integrated system which consists of cryogenic air separation unit, polymer electrolyte membrane electrolyzer and reactor to produce ammonia for a selected case study application in Istanbul, Turkey. A thermodynamic analysis of the proposed system illustrates that electricity consumption of PEM electrolyzer is 3410 kW while 585.4 kW heat is released from ammonia reactor. The maximum energy and exergy efficiencies of the ammonia production system which are observed at daily average irradiance of 200 W/m(2) are found as 26.08% and 30.17%, respectively. The parametric works are utilized to find out the impacts of inlet air conditions and solar radiation intensity on system performance. An increase in the solar radiation intensity results in a decrease of the efficiencies due to higher potential of solar influx. Moreover, the mass flow rate of inlet air has a substantial effect on ammonia production concerning the variation of generated nitrogen. The system has a capacity of 0.22 kg/s ammonia production which is synthesized by 0.04 kg/s H-2 from PEM electrolyzer and 0.18 kg/s N-2 from a cryogenic air separation unit. The highest exergy destruction rate belongs to PEM electrolyzer as 736.2 kW while the lowest destruction rate is calculated as 3.4 kW for the separation column. (c) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Ammonia; Renewable hydrogen; Electrolyzer; Energy; Exergy; Efficiency; POWER; WATER; CYCLE; FUEL; WIND; Chemistry; Electrochemistry; Energy & Fuels